Study of High Nature Value Farmland (HNVf) in Rehabilitation Area, Block Donglo, Meru Betiri National Park - Agung Sih Kurnianto; Hari Purnomo; Nilasari Dewi (Biotropika: Journal of Tropical Biology, 2020)
This study aims to quantitatively analyze the agricultural commodities in the rehabilitation area and their relationship qualitatively in an understanding of biodiversity conservation. The research was held in the Rehabilitation area, Donglo Block, Wonoasri resort, Meru Betiri National Park (-8.41158, 113.67849). Vegetation analysis was held by using a circle method with (r=17.1 m) for trees and 5 square method (1x1 m) for ground cover. We applied the point count method (r=20 m) in this study to observe diurnal birds. Mammal observations were held on each land with an area of 500 m2 by an observer. The observations showed that Jackfruit  Arthocarpus heterophyllus (highest INP = 81.46) provided perch for insectivorous birds: Sooty-headed Bulbul, Black-winged Flycatcher-shrike, and Collared Kingfisher. The average circumference of trees reaches 73 cm and height reaches 8.4 m. Peje Pueraria javanica is a ground cover plant that dominates among other commodities in the Donglo (INP=58.73). Wild boar Sus scrofa and long-tailed monkeys Macaca fascicularis appear in groups (5-20 individuals) as pests. Six of the 9 bird species identified as insectivores. White-bellied Sea-eagle has a role as a carnivore. Only a species has granivore roles.